2023
DOI: 10.1021/acs.jctc.2c00895
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Accuracy of Variational Quantum Eigensolvers with Fewer Qubits Using Orbital Optimization

Abstract: Near-term quantum computers will be limited in the number of qubits on which they can process information as well as the depth of the circuits that they can coherently carry out. To date, experimental demonstrations of algorithms such as the Variational Quantum Eigensolver (VQE) have been limited to small molecules using minimal basis sets for this reason. In this work we propose incorporating an orbital optimization scheme into quantum eigensolvers wherein a parametrized partial unitary transformation is appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Several authors have shown that orbital relaxation is important to reduce VQE errors and the number of qubits . In those studies, the energy of VQE is minimized concerning both cluster amplitudes and orbitals, resulting in a self-consistency that demands higher computational costs than standard VQE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have shown that orbital relaxation is important to reduce VQE errors and the number of qubits . In those studies, the energy of VQE is minimized concerning both cluster amplitudes and orbitals, resulting in a self-consistency that demands higher computational costs than standard VQE.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have shown that orbital relaxation is important to reduce VQE errors 39−42 and the number of qubits. 56 In those studies, the energy of VQE is minimized concerning both cluster amplitudes and orbitals, resulting in a self-consistency that demands higher computational costs than standard VQE. It is thus interesting to examine whether correlated orbital reference preoptimized using a lower-level method can improve the accuracy of "single-shot" VQE.…”
Section: Resultsmentioning
confidence: 99%
“…The idea of a hybrid orbital optimization routine has been explored first by Takeshita et al, and a fully hybrid quantum-classical CASSCF has been reported by Tilly et al where the 1 and 2 body RDMs were sampled independently to mitigate their error and noncanonical orbitals were used. Other quantum multi-configurational SCF implementations have been also reported in the literature. , Nevertheless, to our knowledge, no comparison has been made with the results coming from an orbital-optimized wave function in the quantum measurement after VQE. We have implemented a CASSCF routine (Figure ) that evaluates the 1 and 2 body RDMs as auxiliary operators to the Hamiltonian and uses canonical CASSCF orbitals (and thus in particular natural orbitals within the active space) by default.…”
Section: Quantum Casscf Routinementioning
confidence: 99%
“…In this work, we will add a pivotal milestone to the aforementioned adaptive VQE algorithms by combining the adaptive expansion of the quantum circuit and ensuing optimization of its accompanying {θ i } parameter set with simultaneous optimization of the orbital rotation parameters κ in the variational energy minimization as outlined in eq . In contrast to related recent works within the framework of near-term quantum-computing-driven MCSCF-type approaches, our adaptive, SCF VQE algorithm, denoted in the following as ADAPT-VQE-SCF, greatly benefits from a considerable reduction in the number of two-qubit gates in the final ansatz that are required to reach convergence with respect to chemical precision. Moreover, we not only provide a state-specific energy minimization (eq ) ADAPT-VQE-SCF algorithm but also a SA one that opens up for an optimization of a common set of MOs for a multitude of states i , that is where λ i is a preselected, fixed weighting factor for the i -th state |Φ i ⟩ that satisfy the constraint but are arbitrary otherwise.…”
Section: Introductionmentioning
confidence: 99%